Improving PISA-Like Questions Through Trialmusi Video Context: LRT, Damri and Transmusi - Agustina, Amalia; Zulkardi (Mathematics Education Journal, 2021)
The aims of this study were (1) to generate PISA mathematics quetions of uncertaint context with the integrated data from LRT, Damri and Transmusi (Trialmusi). (2) is there any potential effect from PISA mathematics questions of uncertain context with the integrated data from LRT, Damri and Transmusi (Trialmusi) towards students’ mathematical literacy abilities of junior high school students. The subjects of this research are the students of junior high school number 1 Palembang. This research applied design research with development study type, with 2 steps, preliminary and formative evaluaions steps. In preliminary step, there were analazying the subject research, curriculum, PISA framework, and designing instrumental questions. In formative evaluation step, there were self evaluation, expert reviews and one to one, small group and field test. The data collection in this research apllied walk trough, documentation, observation, interview and test. This research generated PISA math questions of uncertain context. With the valid and practical integrated data from trialmusi. The validation came from the result of validation assessment, which were from context, construct, language and one to one students’ assessment. Practical came from the result of student understanding towards small group question. Then from the students’ answers in the field test steps. DOI: https://doi.org/10.22342/jpm.15.1.11989.91-102